An Overview About the Biology of Skeletal Muscle Satellite Cells - Forcina, Laura; Miano, Carmen; Pelosi, Laura; Musarò, Antonio (Current genomics, 2019)
The peculiar ability of skeletal muscle tissue to operate adaptive changes during post-natal development and adulthood has been associated with the existence of adult somatic stem cells. Satellite cells, occupying an exclusive niche within the adult muscle tissue, are considered bona fide stem cells with both stem-like properties and myogenic activities. Indeed, satellite cells retain the capability to both maintain the quiescence in uninjured muscles and to be promptly activated in response to growth or regenerative signals, re-engaging the cell cycle. Activated cells can undergo myogenic differentiation or self-renewal moving back to the quiescent state. Satellite cells behavior and their fate decision are finely controlled by mechanisms involving both cell-autonomous and external stimuli. Alterations in these regulatory networks profoundly affect muscle homeostasis and the dynamic response to tissue damage, contributing to the decline of skeletal muscle that occurs under physio-pathologic conditions. Although the clear myogenic activity of satellite cells has been described and their pivotal role in muscle growth and regeneration has been reported, a comprehensive picture of inter-related mechanisms guiding muscle stem cell activity has still to be defined. Here, we reviewed the main regulatory networks determining satellite cell behavior. In particular, we focused on genetic and epigenetic mechanisms underlining satellite cell maintenance and commitment. Besides intrinsic regulations, we reported current evidences about the influence of environmental stimuli, derived from other cell populations within muscle tissue, on satellite cell biology.